2023
DOI: 10.3390/su151310548
|View full text |Cite
|
Sign up to set email alerts
|

Determining Factors for Farmers to Engage in Sustainable Agricultural Practices: A Case from Indonesia

Yayat Sukayat,
Iwan Setiawan,
Ukas Suharfaputra
et al.

Abstract: The Green Revolution still heavily influences the agricultural practices of small-scale farming enterprises employing unsustainable methods of cultivation. As a result, many initiatives have been developed to promote more environmentally friendly agricultural practices. This paper aims to seek the determinants of farmers regarding practicing more sustainable farming in Tasikmalaya Regency, Indonesia, especially in terms of the use of chemicals. Data were gained by interviewing 360 farmers at the study site. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…In addition to their influence on the distribution of incentives, farmer groups also play a significant role in enhancing farmers' resilience to safeguarding their land, as these groups facilitate the dissemination of various agricultural programs and knowledge to farmers. Sukayat et al [33] conducted a study on sustainable agriculture and found that the degree of involvement of farmers in farmer groups is a crucial factor influencing the sustainability of agricultural practices. Our findings reveal that farmers residing in mountainous regions and participating in farming groups are more inclined to preserve their agricultural activities.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to their influence on the distribution of incentives, farmer groups also play a significant role in enhancing farmers' resilience to safeguarding their land, as these groups facilitate the dissemination of various agricultural programs and knowledge to farmers. Sukayat et al [33] conducted a study on sustainable agriculture and found that the degree of involvement of farmers in farmer groups is a crucial factor influencing the sustainability of agricultural practices. Our findings reveal that farmers residing in mountainous regions and participating in farming groups are more inclined to preserve their agricultural activities.…”
Section: Discussionmentioning
confidence: 99%
“…There is a complex relationship and mutual influence between sustainable agriculture, local wisdom and education. Sustainable agriculture relates to the principles of wise use of natural resources, environmental conservation, and sustainable living, while local wisdom relates to knowledge and practices that operate traditionally and have been proven to have sustainable value (Castilo, 2016;Khamung & Program, 2015;Prayoga et al, 2020;Sukayat et al, 2023). Education is believed to have an important role in preserving and transmitting local wisdom, while also educating the community to be in harmony with traditional values.…”
Section: Contributions and Recommendationsmentioning
confidence: 99%
“…However, after acknowledging the beneficial effects of organic fertilizers on soil health, emission reduction, and adaptation to climate change (as discussed in Section 4), it becomes necessary for the government to promote their use. This necessitates the implementation of policies aimed at such promotion, including the following [186][187][188][189]:…”
Section: Challenges In Implementing Agroecological Managementmentioning
confidence: 99%